New Applications for Touchscreen in 2D and 3D Medical Imaging Workstations - Hinckley, Ken; Goble, John C.; Pausch, Randy; Kassell, Neal F. (Proc. SPIE Medical Imaging '95: Image Display, 1995)
We present a new interface technique which augments a 3D user interface based on the physical manipulation of tools, or props, with a touchscreen. This hybrid interface intuitively and seamlessly combines 3D input with more traditional 2D input in the same user interface. Example 2D interface tasks of interest include selecting patient images from a database, browsing through axial, coronal, and sagittal image slices, or adjusting image center and window parameters. Note the facility with which a touchscreen can be used: the surgeon can move in 3D using the props, and then, without having to put the props down, the surgeon can reach out and touch the screen to perform 2D tasks. Based on previous work by Sears, we provide touchscreen users with visual feedback in the form of a small cursor which appears above the finger, allowing targets much smaller than the finger itself to be selected. Based on our informal user observations to date, this touchscreen stabilization algorithm allows targets as small as 1.08 mm multiplied by 1.08 mm to be selected by novices, and makes possible selection of targets as small as 0.27 mm multiplied by 0.27 mm after some training. Based on implemented prototype systems, we suggest that touchscreens offer not only intuitive 2D input which is well accepted by physicians, but that touchscreens also offer fast and accurate input which blends well with 3D interaction techniques.